Influence of cinaciguat on gastrointestinal motility in apo‐sGC mice. Issue 11 (8th September 2014) - Cosyns, Sarah M. R.; Huyghe, Leander; Thoonen, Robrecht; Stasch, Johannes‐Peter; Brouckaert, Peter; Lefebvre, Romain A.
Abstract Background Cinaciguat (BAY 58‐2667), an NO‐ and heme‐independent sGC activator, was shown to be more effective when the heme‐group of sGC is oxidized in vascular tissue. In apo‐sGC mice (sGCβ1His105Pheknockin) both sGC isoforms (sGCα1β1 and sGCα2β1) are heme‐deficient and can no longer be activated by NO; these mice, showing decreased gastrointestinal nitrergic relaxation and decreased gastric emptying, can be considered as a model to study the consequence of heme‐oxidation in sGC. Our aim was to compare the influence of cinaciguat, on in vitro muscle tone of gastrointestinal tissues, and on gastric emptying in WT and apo‐sGC mice. Methods Gastrointestinal smooth muscle strips were mounted in organ baths for isometric force recording and cGMP levels were determined by enzyme immunoassay. Protein levels of sGC subunits were assessed by immunoblotting. Gastric emptying was determined by phenol red recovery. Key Results Although protein levels of the sGC subunits were lower in gastrointestinal tissues of apo‐sGC mice, cinaciguat induced concentration‐dependent relaxations and increased cGMP levels in apo‐sGC fundus and colon to a similar or greater extent than in WT mice. The sGC inhibitor ODQ increased cinaciguat‐induced relaxations and cGMP levels in WT fundus and colon. In apo‐sGC antrum, pylorus and jejunum, cinaciguat was not able to induce relaxations. Cinaciguat did not improve delayed gastric emptying in apo‐sGC mice. Conclusions & Inferences Cinaciguat relaxes the fundus and colon efficiently when sGC is in the heme‐free condition; the non‐effect of cinaciguat in pylorus explains its inability to improve the delayed gastric emptying in apo‐sGC mice.